Re-shaping pruning improves the dynamic response of centuries-old olive trees to branch-shaker vibrations application - Camposeo, Salvatore; Vicino, Francesco; Vivaldi, Gaetano Alessandro; Pascuzzi, Simone (Frontiers in Plant Science, 2023)
Very ancient large-size olive trees is a peculiarity of olive growing in the Mediterranean basin; high vigor cultivars are widespread, with training forms poorly adapted to mechanical harvesting by trunk/branch shakers. The significant leaves quantity, the considerable tree height and the presence of multiple dichotomous hanging branches lead to a damping in the transmission of vibrations applied by the branch-shaker machines. To improve the performances of this modern mechanical harvesting method, a re-shaping pruning needs, mainly aimed at removing both the hanging branches and those forming dichotomies. The goal of this study was to investigate through field tests, the dynamic responses of pruned and not pruned very large-size olive trees under different excitation forces. The hypothesis is that a more rational pruning could increase significantly the vibration transmission. We intended offer a first contribution to the knowledge about the dynamic behavior of centuries-old tree skeleton. Tests were conducted on the same trees before and after the re-shaping pruning. The main effect of the pruning was an increase of power spectral density by 10 times in the tertiary branches of pruned trees (range 1.0-10 m s-2) with respect to not-pruned ones (range 0.1-1.0 m s-2) at frequency >50 Hz under vibration excitation; moreover, vibrations decay times (120-150 ms) and amplitude (>10-1 m s-2) were higher under single impulse excitation. These insights could be applied on different horticultural conditions, leading to increase the economic sustainability of monumental olive trees, a key portion of the Mediterranean landscape and cultural heritage, by increasing the efficiency of branch-shaker machines.